Chapter 8 Research Strategies for Investigating Protein Ubiquitination in Lung Diseases - Zhao, Yutong (Taylor & Francis, 2024)
ch. 8 Post-translational modification (PTMs) determines protein's cellular functions including enzyme activity, localization, protein-protein interaction, and protein stability. Ubiquitin is a 7-kDa protein. Ubiquitination is one of PTMs and it is defined as protein covalently conjugation with a ubiquitin or poly-ubiquitin chains. A series of enzymatic reactions catalyze protein ubiquitination, which can be reversed by deubiquitinating enzymes (DUBs). The abnormal expression of ubiquitination-related enzymes and ubiquitination in lung cells have been demonstrated to alter cell functions, such as cell proliferation, death, and differentiation, ultimately contribute to the pathogenesis of lung diseases. In this chapter, we will introduce the methodology and research strategies for investigating protein ubiquitination in lung cells and experimental lung diseases. Common practice and edge-cutting laboratory technologies will be introduced in the chapter. Finally, we will discuss new drug development by targeting ubiquitination for therapies.